Introducing BECCS through HPC to the research agenda: The case of combined heat and power in Stockholm - Fabian Levihn; Linus Linde; Kåre Gustafsson; Erik Dahlen (Energy Reports, 2019)
In the years since COP21 in Paris, awareness of the need for carbon sinks has grown rapidly. However, policy instruments supporting a path to this target are still lacking. Bioenergy carbon capture and storage (BECCS) may provide a way to rapidly reduce global warming. In the Nordics, much of the basic infrastructure for successful BECCS implementation is already in place. So why is not more happening? This study provides insights to barriers and policy implications in relation to successful BECCS implementation. Though implementation could support economic growth and welfare development, the cost is relatively high for individual utilities. In the deregulated competitive heating market in the case of Stockholm, cost transfer to customers is prohibited, effectively impeding implementation. Moreover, while present national or EU-based support schemes could cover investments, the operating cost is high, so other economic policy approaches are required. Lastly, this paper shows that BECCS on combined heat and power plants has a potential, but requires much more research. Thus it is suggested that negative emission technologies in energy systems are brought into research agendas such as the future of combined heat and power and urban multi energy systems.
Keywords: 330; 4GDH; BECCS; CHP; Economic efficiency; Policy